The impact of Covid-19 related policy responses on municipal debt markets - Robert Bernhardt; Stefania D'Amico; Santiago I. Sordo Palacios (Federal Reserve Bank of Chicago, 2021)
Municipal (muni) bonds are an important source of funding for state and local governments. During the Covid-19 pandemic, muni debt markets became severely distressed. In response, the Federal Reserve established the Municipal Liquidity Facility (MLF). Meanwhile, Congress enacted extensive fiscal measures that included direct aid to cities and states. To understand whether and how these policies worked, we employ a state-level regression model to estimate the relative efficacy of monetary and fiscal policy interventions for the term structure of muni-Treasury yield spreads. We find that fiscal and monetary policy together reduced those spreads by as much as 245 basis points. Fiscal policy contributed twice as much as monetary policy to the notable decline in shorter-term muniTreasury spreads. At longer maturities, the contribution of fiscal policy was at least three times as large as that of monetary policy, suggesting that it addressed fundamental credit concerns.
Keywords: E50; G51; H74; 330; Monetary Policy; Policy Effects; Stabilization; Bond Market; Security Markets; Government Bonds; Local Government Bonds